Expression of Biliverdin Reductase A in peripheral blood leukocytes is associated with treatment response in HCV-infected patients - Subhanova, Iva; Muchova, Lucie; Lenicek, Martin; Vreman, Hendrik J; Luksan, Ondrej; Kubickova, Kristyna; Kreidlova, Miluse; Zima, Tomas; Vitek, Libor; Urbanek, Petr (PloS one, 2013)
BACKGROUND AND AIMS: Hepatitis C virus (HCV) infection is associated with systemic oxidative stress. Since the heme catabolic pathway plays an important role in antioxidant protection, we attempted to assess the gene expression of key enzymes of heme catabolism, heme oxygenase 1 (HMOX1), heme oxygenase 2 (HMOX2), and biliverdin reductase A (BLVRA) in the liver and peripheral blood leukocytes (PBL) of patients chronically infected with HCV. METHODS: Gene expressions (HMOX1, HMOX2, BLVRA) and HCV RNA were analyzed in PBL of HCV treatment naïve patients (n = 58) and controls (n = 55), with a subset of HCV patients having data on hepatic gene expression (n = 35). Based upon the therapeutic outcome, HCV patients were classified as either responders (n = 38) or treatment-failure patients (n = 20). Blood samples in HCV patients were collected at day 0, and week 12, 24, 36, and 48 after the initiation of standard antiviral therapy. RESULTS: Compared to the controls, substantially increased BLVRA expression was detected in PBL (p<0.001) of therapeutically naïve HCV patients. mRNA levels of BLVRA in PBL closely correlated with those in liver tissue (r2 = 0.347,p = 0.03). A marked difference in BLVRA expression in PBL between the sustained responders and patients with treatment failure was detected at week 0 and during the follow-up (p<0.001). Multivariate analysis revealed that BLVRA basal expression in PBL was an independent predictor for sustained virological response (OR 15; 95% CI 1.05-214.2; P = 0.046). HMOX1/2 expression did not have any effect on the treatment outcome. CONCLUSION: Our results suggest that patients with chronic HCV infection significantly upregulate BLVRA expression in PBL. The lack of BLVRA overexpression is associated with non-responsiveness to standard antiviral therapy; whereas, HMOX1/2 does not seem to have any predictive potential.
Keywords: játra; ROC Curve; hemoxygenasa-1; exprese genu; Humans; Gene Expression; lidé středního věku; oxidoreduktasy působící na CH-CH vazby; Leukocytes; hem; Female; dospělí; výsledek terapie; Hepatitis C; lidé; Metabolic Networks and Pathways; Adult; ženské pohlaví; Liver; hepatitida C; Male; Middle Aged; antivirové látky; Oxidoreductases Acting on CH-CH Group Donors; Treatment Outcome; Heme Oxygenase-1; hemová oxygenasa (decyklizující); Heme Oxygenase (Decyclizing); Antiviral Agents; metabolické sítě a dráhy; ROC křivka; mužské pohlaví; Heme; Hepacivirus; leukocyty